Dynamic Multipath Resource Management for Ultra Reliable Low Latency Services - Islambouli, Rania (2019)
One of the core novel features of 5G networks is the support of ultra-reliable low latency communications (URLLC). This will pave the way for a plethora of mission critical applications in diverse sectors including health, security, gaming, and manufacturing, among others, through guaranteed premium grade reliability and delay; yet, this requires the development of innovative mechanisms that can address the existing challenges. In this work, we focus on the simultaneous utilization of multiple paths via different wireless interfaces and networks in order to deliver data from source to destination in a timely manner and with high reliability. We formulate the problem as a mixed integer program and generate an optimized strategy to efficiently utilize the resources among the different paths. Simulation results are presented for various scenarios to quantify performance gains with respect to other alternative approaches.